African Union High-Level Implementation Panel for Sudan Press Statement: Sudanese Political Parties and Civil Society Organisations meet to discuss the Referendum and Code of Conduct (Tufts Archival Research Center, 2005)
This press release is about the meeting of several political parties in Sudan to discuss the Code of Conduct for the elections and popular consultation.